Molecular cloning and analysis of small optic lobes, a structural brain gene of Drosophila melanogaster. - Delaney, S.J.; Hayward, D.C.; Barleben, F.; Fischbach, K.F.; Miklos, G.L. (Proceedings of the National Academy of Sciences of the United States of America, 1991)
Mutations in the small optic lobes (sol) gene of Drosophila melanogaster cause specific cells to degenerate in the developing optic lobes, resulting in the absence of certain classes of columnar neurons. These neuronal defects lead to specific alterations in behavioral characteristics, particularly during flight and walking maneuvers. We have isolated the wild-type sol locus by microcloning and chromosomal walking and have established its genetic and molecular limits. Two major transcripts of 5.8 and 5.2 kilobases are produced from this locus by alternative splicing and are present throughout the entire life cycle. Sequence analyses of cDNAs corresponding to these two classes of transcripts predict two proteins of 1597 and 395 amino acids. The first shows similarity in its carboxyl-terminal region to the catalytic domain of a vertebrate calcium-activated neutral protease (calpain), whereas its amino-terminal region contains several zinc-finger-like repeats of the form WXCX2CX10-11CX2C. The second predicted protein contains only the first two of the zinc-finger-like repeats and is missing the calpain domain. By constructing transgenic flies carrying a single wild-type copy of the sol gene in a homozygous sol mutant background, we have restored the normal neuroanatomical phenotype to individuals that would have developed mutant brains.